2017
DOI: 10.1111/nph.14436
|View full text |Cite
|
Sign up to set email alerts
|

Clinal population divergence in an adaptive parental environmental effect that adjusts seed banking

Abstract: Bet-hedging via between-year seed dormancy is a costly strategy for plants in unpredictable environments. Theoretically, fitness costs can be reduced through a parental environmental effect when the environment is partly predictable. We tested whether populations from environments that differ in predictability diverged in parental effects on seed dormancy. Common garden-produced seeds of the two annual plant species Biscutella didyma and Bromus fasciculatus collected along an aridity gradient were grown under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 83 publications
(121 reference statements)
3
72
0
Order By: Relevance
“…In sessile organisms like plants, local adaptation along environmental gradients, such as aridity or temperature gradients, may lead to clinal trait variation. For example, seed dormancy increases linearly with decreasing rainfall in many annual dryland species (Hacker, 1984;Hacker & Ratcliff, 1989;Kronholm, Picó, Alonso-Blanco, Goudet, & De, 2012;Lampei, Metz, & Tielbörger, 2017;Tielbörger, Petruů, & Lampei, 2012;Volis, Mendlinger, & Ward, 2002;Wagmann et al, 2012). Mostly, environmental gradients result from geographical or geological conditions (e.g., elevation differences or rain shadow) that influence local climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In sessile organisms like plants, local adaptation along environmental gradients, such as aridity or temperature gradients, may lead to clinal trait variation. For example, seed dormancy increases linearly with decreasing rainfall in many annual dryland species (Hacker, 1984;Hacker & Ratcliff, 1989;Kronholm, Picó, Alonso-Blanco, Goudet, & De, 2012;Lampei, Metz, & Tielbörger, 2017;Tielbörger, Petruů, & Lampei, 2012;Volis, Mendlinger, & Ward, 2002;Wagmann et al, 2012). Mostly, environmental gradients result from geographical or geological conditions (e.g., elevation differences or rain shadow) that influence local climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Overall demethylation may lead to disruption of the balanced methylation-phenotype link underlying optimal phenotypes under given conditions. The potential epigenetic effects, such as transgenerational plasticity, are also known to strongly vary between genotypes (Becker and Weigel 2012, Lampei et al 2017, Groot et al 2017). Hence, we need experimental studies directly demonstrating the importance of heritable epigenetic variation for species phenotypic response to different climates that consider also genetic control of the epigenetic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in annual species of Israel, seed dormancy varies along a cline in aridity and precipitation variability consistent with adaptive bet hedging (Tielborger et al, 2012). Moreover, in those same species, the relative strength of parental effects on germination also corresponded with the cline in aridity and precipitation variability (Lampei et al, 2017). Our experiments used wild-collected seed from our study populations, so we cannot distinguish the contributions of genetic divergence and transgenerational plasticity across sites.…”
mentioning
confidence: 97%
“…On the other hand, traits that enhance germination in response to reliable environmental cues, such as temperature and precipitation, can act to time germination with favorable conditions, and these traits define the conditions under which germination will proceed. The adaptive value of these traits (bet hedging and germination cueing) depends on the time scale of variation and the reliability of environmental cues (Cohen, 1967;Donaldson-Matasci et al, 2013;Botero et al, 2015), and observed germination strategies likely reflect past selection for bet hedging, germination cueing, or both (Donohue et al, 2010;Lampei and Tielborger, 2010;Gremer et al, 2016;Lampei et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation